Employing laser-accelerated proton beams to diagnose high intensity laser-plasma interactions - Sarri, G; Cecchetti, C; Quinn, K; Norreys, P; Trines, R; Willi, O; Fuchs, J; McKenna, P; Quinn, M; Pegoraro, F; Bulanov, S; Borghesi, M (2012)
A review of the proton radiography technique will be presented. This technique employs laser-accelerated laminar bunches of protons to diagnose the temporal and spatial characteristic of the electric and magnetic fields generated during high-intensity laser-plasma interactions. The remarkable temporal and spatial resolution that this technique can achieve (of the order of a picosecond and a few microns respectively) candidates this technique as the preferrable one, if compared to other techniques, to probe high intensity laser-matterinteractions. © 2012 American Institute of Physics.